Analisis SWOT pada Daya Tarik Wisata di Kawasan Pecinan, Kembang Jepun Kota Surabaya - Ayu Dianapramesti Eksitasari; Desvidyauralia Kartika Indriyana; Made Bambang Adnyana (Departemen Pariwisata Universitas Negeri Padang, 2023)
The Chinese area or Chinatown is located east of the Red Bridge precisely in the Chinatown area, Jalan Kapasan Surabaya. Chinatown area witnessed the civilization of the Chinese community during the Dutch rule and is one of the centers of Chinese culture rich in history and traditional heritage. This study aims to conduct a SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) on tourist attractions in Chinatown, Kembang Jepun Surabaya. The methods used in this study are field observation, and literature study. The collected data is then analyzed with a SWOT approach to identify strengths, weaknesses, opportunities, and threats that affect tourist attraction in Chinatown. The results of the analysis show that Chinatown has several strengths as a tourist attraction, among others: rich cultural and historical heritage, and interesting traditional architecture. However, there are also some disadvantages that need to be considered, such as the lack of tourism supporting facilities. On the opportunity side, Chinatown has the potential for better tourism development through the development of adequate infrastructure and supporting facilities, increased promotion and marketing, and the development of diverse tourism products. However, there are also several threats that need to be watched out for, such as competition with other tourist destinations, changes in tourist trends, and slowing economic growth that can affect tourist visits